Step
*
1
of Lemma
bag-filter-trivial
.....antecedent..... 
1. T : Type
2. p : T ⟶ 𝔹
3. ∀x:T. (↑p[x])
4. as : T List
5. bs : T List
6. permutation(T;as;bs)
⊢ permutation(T;filter(λx.p[x];as);bs)
BY
{ (NthHypEq (-1) THEN EqCD THEN Auto) }
1
.....subterm..... T:t
2:n
1. T : Type
2. p : T ⟶ 𝔹
3. ∀x:T. (↑p[x])
4. as : T List
5. bs : T List
6. permutation(T;as;bs)
⊢ filter(λx.p[x];as) = as ∈ (T List)
Latex:
Latex:
.....antecedent..... 
1.  T  :  Type
2.  p  :  T  {}\mrightarrow{}  \mBbbB{}
3.  \mforall{}x:T.  (\muparrow{}p[x])
4.  as  :  T  List
5.  bs  :  T  List
6.  permutation(T;as;bs)
\mvdash{}  permutation(T;filter(\mlambda{}x.p[x];as);bs)
By
Latex:
(NthHypEq  (-1)  THEN  EqCD  THEN  Auto)
Home
Index